Implementation of Outdoor Games to Improve 4-5 Year Old Childrens Number Sense - Fitri Nurhayati; Harun Rasyid (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2019)
This research implemented some outdoor games, which can improve students number sense, through a quasi-experiment project with one group pretest-posttest design in a kindergarten class (4-5 years old) in Bantul district. The students were invited to participate actively in outdoor games. They can contribute directly to the outdoor games which can develop their competence in number using learner-centred method and supported by the teachers. The right outdoor games can be identified as a way to improve students sense in numbers. Many teachers can also shift their perspectives from the old class management they had.